Toxicological assessment of Pb, Cd and Cr in lettuce and onion grown around Ellala River in Mekelle, Tigray, Ethiopia - Gebreyohannes, Teklay; Gebrekidan, Abraha (Ethiopian Journal of Science and Technology, 2025)
The purpose of this study was to investigate the toxicological effect of Pb, Cd and Cr in vegetables. Water, soil and vegetables samples were collected to determine heavy metal content using FAAS and its impact on human health via consumption of vegetables. The heavy metals for water samples were recorded in the order of Pb>Cd>Cr, and all, except Cd, were found under WHO/FAO limits. Similarly, the heavy metals of soil samples were also recorded in the order of Cr>Cd>Pb, which was under Ewers and EU permissible limits. On lettuce, mean levels of heavy metals were Pb 0.34 ± 0.04 mg/kg, Cd 1.07 ± 0.12 mg/kg and Cr 3.50 ± 0.23 mg/kg were recorded above the WHO/FAO limits. On onion, levels were 0.75 ± 0.05 mg/kg for Pb, 0.41 ± 0.04 mg/kg for Cd and 1.98 ± 0.27 mg/kg for Cr, which were above the WHO/FAO limits. The high metal content could be attributed to high anthropogenic activities. The TF (transfer factor) for the heavy metal in vegetables also showed a trend of Cd>Pb>Cr. The TF of Cd on lettuce ranged between 0.827 and 0.914, because of the high Cd mobility and its high bio-accumulation factor in lettuce. Thus, TF values of vegetables above 0.5 are considered to be contaminated and thus needs for continuous follow-up. However, the health risk index and daily intake rate of heavy metals of the study indicates the vegetables are safe to eat. But, due to the bioaccumulation nature of the heavy metals and the continual use of these vegetables with increase anthropogenic activities and demand of people for vegetables may pose health problem.